Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm currently repeating for exam and i'm stuck with limits of following two sums.

$$\lim_{n\rightarrow +\infty} \sum_{k=0}^n \frac{(k-1)^7}{n^8}$$ and $$\lim_{n\rightarrow +\infty} \sum_{k=0}^n \frac{\sqrt[n]{e^k}}{n}$$

Maybe if sum were from $k=0$ to $\infty$ then i could change it to integral and then calculate it somehow, but i this is a first time i see such task and i'd be greatful for ideas how to solve such tasks... Thank you in advance!

share|improve this question
    
This formula may help you. –  x.y.z... May 7 at 18:51

2 Answers 2

up vote 5 down vote accepted

Hints:

$$\sum_{k=0}^n\frac{\sqrt[n]{e^k}}n=\frac1n\sum_{k=0}^ne^{k/n}\xrightarrow[n\to\infty]{}\int\limits_0^1e^x\,dx$$

I'm assuming the first sum actually begins at $\;k=1\;$ :

$$\sum_{k=1}^n\frac{(k-1)^7}{n^8}=\frac1n\sum_{k=0}^n\left(\frac kn\right)^7\xrightarrow[n\to\infty]{}\int\;\ldots$$

share|improve this answer
1  
Oh man, such a beautiful move! Thank you for this –  Chris May 7 at 19:03
    
if i have $$\sum_{k=1}^n ln((n+k)^{n+k}) \xrightarrow[n\to\infty]{} \int_{ln 4}^\infty x dx$$ is that right? According to that, this sum diverges, right? –  Chris May 7 at 19:14
    
First, I can't see here how that sum equals that integral, second: it's easy to see $\;\log(n+k)^{n+k}\rlap{\;\;\;/}\longrightarrow 0\;$ and thus the series can't converge... –  DonAntonio May 7 at 19:17
    
Yes yes you are right... I wasn't right cause $n,k$ aren't real numbers. Thanks again –  Chris May 7 at 19:39

I did it this way:

Using Faulhaber's formula we have:

$$\sum_{k=1}^n k^p = {1 \over p+1} \sum_{j=0}^p (-1)^j{p+1 \choose j} B_j n^{p+1-j},\qquad \mbox{where}~B_1 = -\frac{1}{2}.$$

From this, we can see the $\sum\limits_{k=1}^{n}k^p$ is a polynomial in $n$ with degree $p+1$ and corresponding coefficient $\dfrac{1}{p+1}$.

Thus,

$$\sum_{k=0}^n \frac{(k-1)^7}{n^8}=\sum_{k=0}^n \frac{k^7}{n^8}+ \frac{P(n)}{n^8},$$ where $P(n)$ is a polynomial in $n$ with degree $\leq 7$. Further:

$$\sum_{k=0}^n \frac{k^7}{n^8}+ \frac{P(n)}{n^8}= \frac{n^8}{(1+7)n^8}+ \frac{Q(n)}{n^8}+\frac{P(n)}{n^8},$$

where $Q(n)$ is a polynomial in $n$ with degree $\leq7$.

Therefore:

$$\lim_{n\to+\infty}\sum_{k=0}^n \frac{(k-1)^7}{n^8}=\frac{1}{(1+7)}=\color{blue}{\frac{1}{8}}.$$

The same strategy is applied for the next summation.

$$\sum_{k=0}^n \frac{\sqrt[n]{e^k}}{n}=\sum_{k=0}^n \frac{{e^{k/n}}}{n}=\sum_{k=0}^n\sum_{p=0}^\infty \dfrac{1}{n}\frac{{(k/n)^p}}{p!}=\sum_{p=0}^\infty\dfrac{1}{p!n^{p+1}}\sum_{k=0}^nk^p.$$

Thus,

$$\sum_{k=0}^n \frac{\sqrt[n]{e^k}}{n}=\sum_{p=0}^\infty\dfrac{1}{p!n^{p+1}}\dfrac{n^{p+1}}{p+1}+\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{R_p(n)}{n^{p+1}}=\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{1}{p+1}+\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{R_p(n)}{n^{p+1}}=\sum_{p=0}^\infty\dfrac{1}{(p+1)!}+\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{R_p(n)}{n^{p+1}},$$

where $R_p(n)$ is a polynomial in $n$ with degree $\leq p$.

Therefore:

$$\lim_{n\to+\infty}\sum_{k=0}^n \frac{\sqrt[n]{e^k}}{n}=\lim_{n\to+\infty}\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{1}{p+1}+\lim_{n\to+\infty}\sum_{p=0}^\infty\dfrac{1}{p!}\dfrac{R_p(n)}{n^{p+1}}=e-1+0=\color{blue}{e-1}.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.